Peningkatan kemampuan representasi matematis mahasiswa pada mata kuliah teori graph dengan e-LKM berbasis konstruktivisme berbantuan Quizizz - Susiaty, Utin Desy; Oktaviana, Dwi (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this study was to determine the increase in students’ mathematical representation skills in graph theory courses with constructivism-based e-LKM assisted by Quizizz. This research is an experimental study with a one group pretest-posttest design. The samples in this study were students of class B Morning semester VI Mathematics Education Study Program IKIP PGRI Pontianak with cluster random sampling technique. The results showed that students obtained pretest and posttest scores for the ability of number patterns with an average of 48.79 and 65.00. After applying constructivism-based learning with constructivism-assisted Quizizz to students’ mathematical representation abilities in the graph theory course, they get a value of t = 4.791 where = 0.05 with t arithmetic > t table (4.791 > 1.701) then H0 is rejected. Thus, learning with constructivism-based e-LKM assisted by Quizizz in the graph theory course can improve students’ mathematical representation skills.